The Reconstruction of Law Number 7 of 2012 Concerning Social Conflict Handling in Indonesia - Utama, Anang Puji (Borong Newinera Publisher, 2025)
Various social conflicts that have occurred in Indonesia have prompted the Government to pass Law Number 7 of 2012 concerning Handling Social Conflicts. Along with the development of technology, information, and communication, it has resulted in rapid social changes, including the use of social media in communication. The aim is to analyze legislative arrangements and the need to reconstruct Law Number 7 of 2012 concerning Handling Social Conflicts. To respond to growing conflicts due to technology, information, and communication, comprehensive arrangements are needed so that conflicts are easily detected and can be resolved immediately. Thus, the reconstruction meaning of Social Conflict is needed as regulated in Law Number 7 of 2012 concerning Handling Social Conflict. By reconstructing the meaning of Social Conflict, it is hoped that the meaning of Social Conflict will be realized as a result of social changes resulting from advances in technology, information, and communication.